2011
DOI: 10.1039/c1ee01428e
|View full text |Cite
|
Sign up to set email alerts
|

FeN nanoparticles confined in carbon nanotubes for CO hydrogenation

Abstract: Cubic FeN particles of a few nanometers in size were synthesized for the first time by encapsulation inside carbon nanotube (CNT) channels. Such an FeN catalyst exhibits a 5-7 times higher activity than a reduced Fe catalyst and a SiO 2 supported iron nitride in CO hydrogenation. The confined FeN catalyst is also more active than iron nitride particles dispersed on the CNT exterior walls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 29 publications
4
68
0
2
Order By: Relevance
“…Briefly, aqueous solution of Fe(NO 3 ) 3 was introduced into the CNT channels by utilizing the capillary forces of CNTs aided by ultrasonication and stirring. Following controlled drying at 140 • C in air, a reported temperature-programmed-reaction (TPRe) method was adapted for the nitridation of these precursors to obtain iron nitride [11]. The sample was heated in a quartz tube reactor at 450 • C for 2 h in 50 ml/min ammonia stream.…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, aqueous solution of Fe(NO 3 ) 3 was introduced into the CNT channels by utilizing the capillary forces of CNTs aided by ultrasonication and stirring. Following controlled drying at 140 • C in air, a reported temperature-programmed-reaction (TPRe) method was adapted for the nitridation of these precursors to obtain iron nitride [11]. The sample was heated in a quartz tube reactor at 450 • C for 2 h in 50 ml/min ammonia stream.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…The catalysts were prepared following the previously reported procedure [7,11,[26][27][28]. Briefly, aqueous solution of Fe(NO 3 ) 3 was introduced into the CNT channels by utilizing the capillary forces of CNTs aided by ultrasonication and stirring.…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the channels of CNT may provide an environment to prolong the contact time of the reactants with metal component inside the tubes, leading to higher selectivity to + 5 C hydrocarbons. The catalytic performance of cubic iron nitride NPs inside and outside CNT was also in accordance to the confinement effect as expected [135]. A striking enhancement of the catalytic activity of Rh-Mn particles confined inside CNTs for the conversion of syngas to C 2 oxygenates was also reported [136].…”
Section: Carbon Support Effectmentioning
confidence: 53%
“…[7] The rigid nanotubes exert as patial restriction on the metal particles, hampering their aggregation,a nd develop interactions between the encapsulatedm olecules and the nanotube surfaces ( Figure 1c). [8] Bao reported that confining metal nanoparticles inside CNTsr esultsi ni mproved catalytic activity with respect to the same metals deposited on the CNTse xterior surface. [9] Our group demonstrated that Ni nanoparticles confined in Al 2 O 3 nanotubes and also embedded in the cavities of the inner walls of Al 2 O 3 nanotubes have striking catalytic performance in hydrogenation reactions.…”
mentioning
confidence: 99%